An examination of dreams and visions in the novels of Virginia Woolf - Dale-Jones, Barbara (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1996)
This thesis explores the importance of the visionary experience in five novels by Virginia Woolf. In her fiction, Woolf portrays the phenomenal world as constantly changing and she uses the cycles of nature and the passing of time as a terrifying backdrop against which the mutability and transience of human life are set. Faced with the inevitability of change and the fact of mortality, the individual seeks moments of permanence. These stand in opposition to flux and lead to the experience of a visionary intensity. Woolf's presentation of time as a qualitative phenomenon and her stress on the importance of memory as a function which allows for the intermingling of past and present make possible the narrative rendering of moments which contradict perpetual change and the rigours of sequential time. Moments of stillness 'occur in the midst of and in spite of process and allow for individual contact with an experience that defies the relentless progression of time. Necessary for this experience is not only memory but also the imagination, a faculty which has the power to perceive patterns of harmony in the midst of the chaos that characterises the phenomenal realm. Fundamental to Woolf's writing, however, is the acknowledgement that visions are fleeting, as are the glimpses of meaning that emerge from them. Therefore, while several of her novels describe the artistic effort to create a structured order as a defense against change, Woolf uses the artist's struggle as a metaphor for the difficulties attached to describing the enigma that is life. None of her artist figures is able to formulate a construction that either sums up life or provides a permanence of vision. This study presents a chronological examination of the novels in order to demonstrate that the changing forms of Woolf's fiction trace the evolution of a style that accurately portrays both the workings of the human mind and the insubstantial and fragmentary nature of life. The chronology also reveals that her novels develop in terms of their presentations of the visionary experience. Woolf's final novel incorporates into its central vision the paradoxical fact of the permanence of time's progression and acknowledges that, beyond the individually mutable life, is a continuum that links pre-history to the future. This notion, which is explored in part in the earlier novels, but developed completely in Between the Acts, suggests that consolation can be found in the greater cycles of existence despite the fact of individual mortality.
Keywords: Woolf, Virginia, 1882-1941 -- Criticism and interpretation; Dreams in literature Visions in literature